The impact of different gastrointestinal reconstruction techniques on gut microbiota after gastric cancer surgery - Yang, Yu; Zhou, Hang-Yu; Zhou, Guo-Min; Chen, Jin; Ming, Rui; Zhang, Dong; Jiang, Huai-Wu (Frontiers in Microbiology, 2025)
IntroductionGastric cancer is one of the common malignant tumors in the digestive tract, characterized by high incidence and mortality rates. This is particularly significant in China, where a large proportion of global new cases of gastric cancer and related deaths occur. In recent years, with the continuous development of molecular biology technology, people have gained a deeper understanding of the gastrointestinal microbiome, and studies have shown that it is closely related to the occurrence, development, and therapeutic response of gastric cancer. Although surgical intervention is crucial in significantly extending the survival of gastric cancer patients, the disruption of the balance of the intestinal microbiota caused by surgery itself should not be overlooked, as it may affect postoperative recovery.MethodsThis study was approved by the Biomedical Ethics Committee of Sichuan Mianyang 404 Hospital. A random sampling method was used to select patients who underwent gastric cancer surgery at the hospital from January 2023 to December 2023. All patients signed written informed consent forms. Standardized perioperative management was conducted for the patients in the study, including preoperative preparation, intraoperative handling, and postoperative treatment. Fecal samples were collected from patients before surgery (before bowel preparation) and around one week after surgery for 16S rRNA sequencing analysis, through which differential biomarkers and related functional genes were sought.ResultsThe study results indicated that there was no significant difference in the diversity of the gut microbiota between the two groups. Compared with the R-Y group, the DTR surgical method significantly altered the structure of the gut microbiota, affecting the types, quantities, and proportions of intestinal bacteria. Furthermore, the DTR group exhibited poorer postoperative nutritional absorption capacity compared to the R-Y group, as indicated by a lower F/B ratio. The R-Y group showed a richer abundance of Bacteroidetes and a lower abundance of Proteobacteria, as well as a higher F/B ratio after surgery. These findings provide new insights into the changes in the gut microbiota following gastric cancer surgery, which may be of significant importance for postoperative recovery and long-term health management.DiscussionThis study reveals the impact of different gastrointestinal reconstruction techniques on the postoperative gut microbiota of gastric cancer patients, providing new insights into the physiological changes during the postoperative recovery period. Although there was no significant difference in microbial diversity between the DTR group and the R-Y group, the DTR group showed more pronounced changes in microbial structure postoperatively, which may be associated with an increased risk of postoperative infection. These findings emphasize the importance of considering the impact on the gut microbiota when selecting gastric cancer surgery methods. However, the study had a limited sample size and did not delve into changes in metabolites. Future studies should expand the sample size and conduct metabolomic analyses to further validate these preliminary findings.